XAS and EPR in Situ Observation of Ru(V) Oxo Intermediate in a Ru Water Oxidation Complex. Issue 3 (29th December 2021) - Levin, Natalia; Casadevall, Carla; Cutsail, George E.; Lloret‐Fillol, Julio; DeBeer, Serena; Rüdiger, Olaf
Abstract: Invited for this month's cover picture are the Rüdiger‐DeBeer‐Lloret groups. The cover shows a periodic table and the complementary XAS and EPR obtained by in situ spectroelectrochemistry to confirm the participation of the Ru(V) oxo in the catalytic water oxidation by this Ru molecular catalyst. Read the full text of the Communication at 10.1002/celc.202101271 . Abstract : "The complementary Electron Paramagnetic Resonance (EPR) and X‐Ray absorption spectroscopies employed under in situ electrochemical conditions granted access to intermediate species arising in the catalytic cycle of a Ru‐based mononuclear water oxidation catalyst. Our findings allow the characterization of a highly reactive Ru(V) oxo intermediate resulting from a water nucleophilic attack and of the species preceding it in the oxidation cascade…" Learn more about the story behind the research featured on the front cover in this issue's Cover Profile. Read the corresponding Communication at 10.1002/celc.202101271 .